Preparation, Properties, and Applications of Graphene-Based Hydrogels - Liao, Guochao; Hu, Junfeng; Chen, Zhou; Zhang, Ruiqian; Wang, Guanchun; Kuang, Tairong (Frontiers in Chemistry, 2018)
As a new carbon-based nanomaterial, graphene has exhibited unique advantage in significantly improving the combination properties of traditional polymer hydrogels. The specific properties of graphene, such as high electrical conductivity, high thermal conductivity and excellent mechanical properties, have made graphene not only a gelator to self-assemble into the graphene-based hydrogels (GBH) with extraordinary electromechanical performance, but also a filler to blend with small molecules and macromolecules for the preparation of multifunctional GBH. It fully exploits the practical applications of traditional hydrogels. This review summarizes the preparation methods, properties, and the applications of GBH. Further developments and challenges of GBH are also prospected.